Increased osseointegration effect of bone morphogenetic protein 2 on dental implants: An in vivo study - Yoo, Daniel; Tovar, Nick; Jimbo, Ryo; Marin, Charles; Anchieta, Rodolfo B.; Machado, Lucas S.; Montclare, Jin; Guastaldi, Fernando P. S.; Janal, Malvin N.; Coelho, Paulo G. (Wiley, 2013)
Application of recombinant human bone morphogenetic protein 2 (rhBMP-2) to implant surfaces has been of great interest due to its osteoinductive potential. However, the optimal coating methodology has not been clarified. The objective of the study was to determine whether the application of rhBMP-2 onto plasma-sprayed hydroxyapatite implant surfaces by immersion in protein solution before implant installation would result in significantly improved bone apposition. Using a sheep iliac model, titanium (Ti) and plasma-sprayed calcium-phosphate (PSCaP)-coated implants uncoated and coated with rhBMP-2 were assessed for their osteogenic effects in the peri-implant area over time in terms of osseointegration and de novo bone formation. After 3 and 6 weeks postoperatively, the samples were retrieved and were subjected to bone-to-implant contact (BIC) and bone area fraction occupancy (BAFO) evaluation. When rhBMP-2 was applied to the PSCaP surface, significant increases in BIC and BAFO were observed at 3 weeks in vivo, whereas when adsorbed directly onto the titanium implant surface, rhBMP-2 did not as effectively improve the bone response (although significantly higher than control Ti). The outcomes of the present study suggested that the combination of plasma-sprayed calcium-phosphate surface and rhBMP-2 coating significantly enhanced osseointegration, which validated the postulated hypothesis. © 2013 Wiley Periodicals, Inc.
Keywords: Bioactivity; Bone morphogenic protein; Calcium-phosphate; Implant surface modification; Release kinetics